Experiment Study of Outburst Pulverized Coal-Gas Two-Phase Flow and Characteristic Analysis of Outburst Wave - Xusheng Zhao; Jie Cao; Bo Wang; Xuelin Yang (Geofluids)
Coal and gas outburst is still a major safety problem in the process of coal production in China. Correctly understanding of the migration law of outburst high gas and pulverized coal is an important basis for accurately predicting the occurrence time and possible scope of outburst. To reveal the airflow disturbance characteristics and coal-gas flow rule in coal and gas outburst process, outburst coal-gas migration simulations under different gas pressures were conducted using a self-developed visual outburst dynamic effect test device. The results showed that coal-gas flow state at the outburst port is divided into subcritical flow, critical flow, and supercritical flow state. The pulverized coal-gas flow migration in the roadway space can be divided into coal gas two-phase flow area, air compression area, and undisturbed area. Under the experimental conditions, the maximum propagation velocities of wave are 342.22~359.21 m/s, and the coal gas two-phase flow is far less than the propagation velocities of outburst wave, just 3.68~33.33 m/s. When the outburst energy is large, multiple compression waves can superimpose to form shock waves. The peak value of the wave does not necessarily appear in the first boosting range. The presence of pulverized coal leads to a faster attenuation of shock wave, but it makes a greater dynamic destructive force at the same speed.